Colaboração Interprofissional no Sistema Municipal Saúde Escola de Sobral - Torres, Jander Magalhães (2012)
The concept of Health System School can be defined as a management strategy idea whose strength is to transform all health services in areas of teaching and learning, with the aim of improving the quality of service, professional development of health workers and provide contextualized training professionals according to the needs of the Unified Health System (SUS). In Sobral, city university vocation that is home to two higher education institutions (HEIs) public and two private, structuring Health System School started from the implementation of a process of continuing health education in the late 1990s, Concomitant to the municipalization process. A remarkable fact was the creation of the School of Education in Family Health Vicomte de Savoie (EFSFVS) in 2001, which later took over the coordination of the integration of teaching and health services. The aim of this study was to assess interprofessional collaboration between health managers and higher education, academics and health professionals in the Municipal Health System School of Sobral. This is a case study, based on a review of documents, interviews with health managers and HEI and self-completed questionnaires applied to teachers and managers of health centers that receive students, conducted between January 2011 and June 2012. The methodology of data analysis was thematic analysis, grounded in theoretical model built by (D'AMOUR, Goulet ET AL. 2003; D'AMOUR, screwed-VIDELA ET AL. 2005; D'AMOUR, 2008) as reference for analyzing interprofessional collaboration processes. As a product of the analysis of the results it was found that shared goals and vision, of the dimensions of interprofessional collaboration, seem to be stronger among managers or leaders Formal System Municipal Health and HEI among professionals that tip. In Governance dimension, the centrality and leadership in fostering the integration between health services and IES was very present in the discourse of managers both managers and teachers agreed that there is support for the process of collaboration, having been cited logistical support and encouragement by the managers. The lack of financial incentive as recovery of the health professional who guides students was mentioned as weakness. The existence of devices covenants and an ordinance regulating the teaching-service integration, improved support for shared action. In the group management has been found that there is a consolidation of discussion spaces in formal permitting the exchange of experience, especially in terms of assessing the collaborative work to improve planning.